No Risk, No Fun? Foreign Direct Investment in Central and Eastern Europe - Jutta Günther; Maria Kristalova (Intereconomics, 2016)
In the course of transition from planned economies to market economies, foreign direct investment played an important role and contributed to international economic integration in Central and Eastern Europe. This paper investigates the determinants of FDI in Central and Eastern Europe, a region which in large part still lacks strong institutions. The empirical analysis presented in this article fi nds evidence that country default risk is not necessarily a hindrance to FDI. In contrast, factors like market size, labour cost and trade liberalisation do matter for FDI engagement in the region.
Keywords: 330; Auslandsinvestition; Wirtschaftliche Anpassung; Länderrisiko; Osteuropa